Hepatic artery pseudoaneurysm after hepatic transplant - endovascular treatment with graft stenting - Campos, Nuno (2023)
Hepatic artery pseudoaneurysms (HAP) after liver transplantation are rare and associated with high mortality. Different treatment options exist for HAP, which include surgical intervention, radiological coil embolization or stenting  and retransplantation. We describe a case of a patient presenting with HAP after a liver transplantion, that was successfully treated with stent grafting, allowing preservation of the arterial flow and minimal risk of organ failure. Endovascular intervention of HAP should be regarded as the treatment of choice, either in symptomatic or in asymptomatic patients.